Influence of Flipped Classroom Method on Nursing Students' Learning Approaches - Shadi Dehghanzadeh (Kerman University of Medical Sciences, 2018)
Background Active learning approaches, including the flipped classroom, can enhance meaningful learning among students of medical sciences. Objectives The purpose of this study was to investigate the effect of the flipped classroom teaching method on nursing students' learning approaches. Methods This one-group quasi-experimental study with a pretest-posttest design was carried out among 46 undergraduate nursing students who had passed the orthopedic nursing course in the academic year of 2017-2018. The participants were selected by the census method. To teach through the flipped classroom method, the instructor provided electronic content for the course using the Articulate Storyline software. Students studied electronic contents and the reference book prior to each session and participated in predetermined collaborative activities. Data were collected using the Revised Two-Factor Study Process Questionnaire (R-SPQ-2F) before and after the completion of the classes. Data were analyzed using descriptive statistics, independent test, paired test and Pearson correlation coefficient by SPSS software. Results The flipped classroom method significantly increased the deep learning approach (P